Autophagy in periodontal disease: Evidence from a literature review. (June 2019) - Lorenzo-Pouso, Alejandro I.; Castelo-Baz, Pablo; Pérez-Sayáns, Mario; Lim, Jason; Leira, Yago
Highlights: Autophagy is related to the periodontal disease pathogenesis according to recent evidence. Autophagy plays a pivotal role in the fight against pathogens and can link periodontitis to several systemic diseases. Autophagy interference may be of help in the search of novel host modulation therapies. Abstract: Objective: To summarize evidence and data relating to the implications of autophagy in periodontal disease (PD) and to describe potential nutraceuticals or pharmaceuticals that could modulate this cell death subtype. Design: Literature searches of various electronic databases (Medline via PubMed, SCOPUS, Web of Science, and EMBASE) using appropriate keywords (e.g., periodontal disease, periodontitis, alveolar bone loss, periodontal infection, tooth loss, autophagy, programmed cell death, and type 2 cell death) were performed. Then, a comprehensive literature review of the current understanding of this link was elaborated. Results: Autophagy plays a pivotal role in PD, and its regulation seems to be an interesting avenue for future periodontal research, according to several in vivo and in vitro reports. Conclusion: Today's research has ascertained the role of autophagy in PD, especially its role in the host's defence against periodontal disease drivers. A bulk of the research recognised several pharmaceuticals and nutraceuticals that could potentially modulate this kind of cell death and serve as useful therapies. However, further research is warranted to reach a clinical translation, which could help in the discovery of novel host modulation therapies for PD.